Publication bias in five dental implant journals: An observation from 2005 to 2009 - Yuan, Judy Chia-Chun; Shyamsunder, Nodesh; Barão, Valentim Adelino Ricardo [UNESP]; Lee, Damian J.; Sukotjo, Cortino (My University, 2011)
Purpose: This study evaluated possible publication bias and its related factors in implant-related research over time. Materials and Methods: Articles published in Clinical Implant Dentistry and Related Research, Clinical Oral Implants Research, Implant Dentistry, Journal of Oral Implantology, and The International Journal of Oral & Maxillofacial Implants between 2005 and 2009 were reviewed. Nonoriginal articles were excluded. For each article included, study outcome, extramural funding source, type of study, and geographic origin were recorded. Descriptive and analytic statistics (a = .05), including the chi-square test and logistic regression analysis, were performed where appropriate. Results: From a total of 2,085 articles, 1,503 met the inclusion criteria. Of the articles analyzed, 1,226 (81.6%), 160 (10.6%), and 117 (7.8%) articles reported positive, negative, and neutral outcomes, respectively. In vitro studies, studies from Asia, and funded animal studies were more likely to report positive outcomes compared to others (P = .02, P < .0001, and P = .009, respectively). Industry-funded studies represented the lowest frequency of positive outcomes versus studies funded by other sources. Conclusions: There were a high number of implant-related studies reporting positive outcomes in the five selected journals. Some selected factors were associated with positive outcome bias. In general, funding was not associated with a positive outcome, except for animal studies. Industry-supported research did not show any association with the publication of positive outcomes. © 2011 by Quintessence Publishing Co Inc.
Keywords: Dental implants; Funding; Industry; Publication bias